2016
DOI: 10.1093/cvr/cvw065
|View full text |Cite
|
Sign up to set email alerts
|

miR-223–IGF-IR signalling in hypoxia- and load-induced right-ventricular failure: a novel therapeutic approach

Abstract: These findings highlight the early role of pulmonary and right-ventricular miR-223 and the IGF-IR in the right heart failure programme initiated by pulmonary hypoxia and increased mechanical load and may lead to the development of novel therapeutic strategies that target the development of PH and right heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…Changes in miR-322-5p are not the only ones that occur in cardiac hypertrophy that are likely to affect the IGF-1 signalling system. For example, miR-223 is a miRNA that is suppressed by hypoxia but targets the IGF-1R [41]. Overexpression of this miRNA attenuated cardiac hypertrophy and suppressed IGF-1R expression in analogous way to the effects of miR-322-5p in response to MCT.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in miR-322-5p are not the only ones that occur in cardiac hypertrophy that are likely to affect the IGF-1 signalling system. For example, miR-223 is a miRNA that is suppressed by hypoxia but targets the IGF-1R [41]. Overexpression of this miRNA attenuated cardiac hypertrophy and suppressed IGF-1R expression in analogous way to the effects of miR-322-5p in response to MCT.…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports found that miR-223 was down-regulated in human PAH lungs, in both the right heart and lungs from rodent models of PH. Downregulation of miR-223 triggers PARP-1 and insulin-like growth factor 1 receptor (IGF-1R) overexpression, subsequent pathologic DNA damage repair, and increased proliferation [32, 33]. The relationship between miRNAs and target genes in vivo is a complex network.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis by genetic means, we conducted experiments in iCM-IGF1RKO mice; i.e., mice with an inducible, cardiomyocyte-restricted deletion of the IGF1R gene (Igf1r). 11,12 Compared with WT mice, iCM-IGF1RKO mice did not show differences in cardiac function at baseline ( Figure 3; Table S2). Although IGF1 treatment improved cardiac functional parameters such as EF and FAC (Figures 3B-3D; Table S3) in wild-type (WT) mice after AMI as before, we unexpectedly found that IGF1 treatment also preserved these functional parameters in iCM-IGF1RKO mice.…”
Section: Igf1 Protects the Heart After Ami Independent Of Igf1r Signamentioning
confidence: 95%